EVALUASI KEBIJAKAN PROGRAM KELUARGA HARAPAN KOTA PALU - Agusta Sri Astuti (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The ideal system built at PKH involves KPM and social assistants and involves the Government, from the ministry to the sub-district/village level. This system moves as a unit towards alleviating poverty. This research aims to determine the evaluation of PKH in Palu City in reducing poverty levels. This research was applied to a qualitative descriptive approach. The definition of the concept by applying the concept of policy evaluation theory by Dunn (2003) includes several criteria, namely effectiveness, efficiency, adequacy, equity, responsiveness and appropriateness. The research results show that the evaluation of Palu City's PKH policy has had a positive impact on poverty alleviation. This can be seen from the fact that all KPM in Palu City have received social assistance for adequate health and education services. Even though there are still several obstacles in it, it is hoped that Palu City PKH activities will be further maximized and also provide motivation for all Palu City KPM towards the spirit of the principle of independence. Keywords: Evaluation, Policy, Family of Hope Program, Beneficiary Families.